A Comprehensive Review on the Impact of Gap Parameters for Multiple Types of Roundabouts in Different Traffic Conditions - Mahbub Hassan; Nafees, Abdullah Al; Shraban, Saikat Sarkar; Mahin, Hridoy Deb; Paul, Arpita; An, Hong Ki (International Journal of Integrated Engineering, 2024)
The increasing number of vehicle owners due to population growth has significantly impacted traffic patterns worldwide. As a result, roundabouts have emerged as popular intersection designs, offering operational simplicity and fewer conflict points compared to traditional unsignalized intersections. This study examines the impact of gap parameters, which are key parameters for evaluating roundabout capacity, on various types of roundabouts across diverse traffic scenarios. Beginning with a historical overview of roundabouts and gap acceptance behavior, the review explores a range of methodologies, including computer simulations, real-world observations, and mathematical models, to gain insights into traffic flow dynamics and vehicle behavior. Additionally, the review analyzes the evolution of roundabout design and geographical disparities, highlighting the multitude of factors influencing roundabout performance. This review aims to provide valuable insights gathered from previous research on how gap parameters influence the performance of different roundabouts. Finally, it highlights the essential role of gap parameters in maximizing roundabout efficiency to benefit all road users, offering valuable insights for researchers and enthusiasts seeking deeper comprehension of roundabout dynamics.